Answer: See bolded below
Explanation:
With the given f(x) and g(x) given, we can directly plug them in to solve. The inverse is to replace the y with x and x with y, then solve for y.
A. f(g(-4))=143
g(-4)=3(-4)+1
g(-4)=-12+1
g(-4)=-11
With g(-4), we plug that into f(x) to find f(g(-4)).
f(-11)=(-11)²-2(-11)
f(-11)=121+22
f(-11)=143
------------------------------------------------------------------------------------
B. 9x²-1
(3x+1)²-2(3x+1)
(9x²+6x+1)-6x-2
9x²-1
------------------------------------------------------------------------------------
C. g⁻¹(x)=(x-1)/3
x=3y+1
x-1=3y
(x-1)/3=y